ANALYSIS OF STRUCTURAL EQUATION MODELING (SEM) THAT INFLUENCE THE MANAGEMENT EFFICIENCY OF ELECTRONIC INDUSTRY EXECUTIVE - Rusmee, Kwanruan; Thurapaeng, Chertchai; Chutchavong , Vanvisa (Life Sciences and Environment Journal, 2022)
This research aims to 1) identify the relationship between human resource management (HRM) practices, and motivational and efficiency of management, and 2) analyze the structural equation modeling (SEM) of factors that affect the efficiency of management of electronics industry management performance, The study used random samples from electronic industry executives 460 persons. The research tool included observation from the tool with reliability of 0.858. Data from the observation from were analyzed by using percentages, arithmetic mean, standard deviation and structural equation modeling (SEM). The research results revealed the following: 1) The relationship of variables, motivation factors, hygiene factors (HF) and human resource management (HRM), was statistically positively correlated with electronics industry management performance, with statistical significance at the .01 level. 2) Structural equation modeling (SEM)of factors influencing the efficiency of management (EFF) of electronics industry management performance was consistent with empirical data (Chi-square = 68.185, Chi-square/df = 1.337, df = 51, p = .069, GFI = .992, CFI = .996, RMR = .032, RMSEA = .037). The incentive variables, support variables, and human resource management explain the variance in the efficiency of electronic industry management by 91.10%.